Сільська початкова школа в системі освітніх трансформацій (середина ХІХ – початок ХХ ст.) - Берладин, Ольга; Berladin, O.B. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджується ґенеза та сутність сільських початкових шкіл (середина ХІХ початок ХХ ст.). Звернення до історико-педагогічної спадщини створення і розвитку початкових освітніх закладів продиктовано вагомістю уроків, які необхідно засвоїти при моделюванні діяльності сучасних початкових шкіл сільської місцевості. The article examines the genesis and nature of rural primary schools (middle of the nineteenth early twentieth century.). Appeal to the historical heritage and educational establishment and development of educational institutions of primary importance is dictated lessons be learned in modeling of modern primary schools in rural areas. Purpose of the article - to analyze the genesis educational transformation in rural primary schools within the appointed time field and on the basis of this outline promising possibility of using historical and educational experience in optimization and modernization. The author reveals the role and place of the parish and district schools in primary education, enabling to use the experience of these schools for modern pedagogy and school practices, including activities in primary schools in rural areas. Retrospective analysis of historical and educational research activities of parish schools gives reason to believe that these schools played an important role in implementing basic education, particularly in rural areas. The main terms of expanding the network of parish schools were the democratization of society caused by the reform of 1861, the recovery of socio-economic and cultural life, the development of industrial and agricultural production, which determined the need to expand educational qualifications of the population, especially in rural areas. Rural schools were giving somewhat broader knowledge: in addition to the law of God, children were taught to read, write, count. On the reading lessons yhey were gaining some knowledge of history, science, geography, studying native culture, so-called optional subjects were introduced: gymnastics, crafts, needlework (for girls), gardening, manual labor, joinery, gymnastics, singing. Progressive Ukrainian public, cultural, educational, economic society and religious organizations promoted and funded the establishment of private Ukrainian folk school. The problems of the educational policy of the nineteenth and early twentieth century are analyzed, the development of primary education in rural areas, the originality and identity of Ukrainian concepts, types of primary school, which is important reaserch in modeling of modern primary schools in rural areas. Their objective historical and pedagogical analysis, further creative use of the results of the new requirements and opportunities will enable the state to update and optimize quality educational socio-cultural environment of modern primary school in rural areas.
Rural Primary School in Educational Transformations (mid XIX - XX centuries).
Keywords: церковнопарафіяльні школи; parish schools; земські школи; земська концепція освіти; початкові школи сільської місцевості; rural schools; rural education concept; primary schools in rural areas